The Influence of Understanding Level on the Development of Mobile-Based E-Money Technology Services (OVO Case Study) - Jawa, Paimen; Syahputra, Dinur; Rambe, Aripin (Journal of Technology and Computer, 2025)
This study examines the influence of understanding level (X₁) and perceived usefulness (X₂) on the adoption of mobile-based e-money services, using OVO in Sumbul District, Indonesia, as a case study. Employing a quantitative causal-comparative design grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT2), the research surveyed 100 OVO users through stratified random sampling. Results indicate that both understanding (p=0.033, β=0.211) and usefulness (p=0.000, β=0.385) significantly enhance usage interest (Y), with their combined effect further validated by regression analysis (F-statistic=14.457). Demographic trends reveal higher adoption among tech-savvy males (52%) aged 36–45 (53%) with bachelor’s degrees (54%), underscoring the role of education and age in digital payment adoption. The study highlights practicality, time efficiency, and long-term benefits as key drivers, aligning with technology acceptance theories. However, barriers persist in rural areas and among less-educated populations, suggesting the need for targeted financial literacy programs and infrastructure improvements. These findings offer actionable insights for policymakers, fintech providers, and businesses aiming to accelerate Indonesia’s transition to a cashless economy. The research contributes to fintech adoption literature by contextualizing behavioral factors in emerging markets, emphasizing the interplay of cognitive, attitudinal, and demographic variables in e-money adoption.